Sistem Informasi Geografis Pengukuran Bidang Tanah Menggunakan Metode Haversine Formula Pada Dinas Pertanahan Kabupaten Aceh Besar Berbasis Web - Cut Riska Ramadhani; Yuswardi; Maryanti (Yayasan Sagita Akademia Maju, 2024)
The Aceh Besar District Land Agency is a government agency that has the task of administering affairs in the agrarian or land and spatial planning sector in government to assist the president in administering state government. The Department of Land Affairs manages state property, namely land. Management is done by means of measurement. Measurements are usually done manually. This requires quite a long time because you have to take measurements by spreading a tape measure according to the plot of land and requiring more than one person to measure it. In this study, the calculation of land area uses the haversine formula method, the haversine formula is a method for determining the distance between two points by taking into account that the earth is not a flat plane but is a plane that has a degree of curvature. The haversine formula method calculates the distance between 2 points based on the length of the straight line between the 2 points on longitude and latitude. The system is designed web-based so that the results of a GIS-based application are obtained to be able to map and carry out land surveying measurements on digital images.